Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.31584/smj.2018.36.1.768
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenias’ Quality of Life and Emotional Intelligence in Songklanagarind Hospital

Abstract: Objective: To estimate the level of quality of life (QoL), emotional intelligence (EI) and the association between QoL and EI in schizophreniaMaterial and Method: A cross-sectional study was conducted at the outpatient department of Songklanagarind Hospital from; May to November, 2016. A total of 96 participants were interviewed. Demographic data and medical history were collected. QoL and EI were assessed using the WHO QOL BREF (Best available techniques REFerence document) Thai version and the Thai EI Screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…In contrast, the stigma of taking medication and having poor or no social support were found to negatively influence adherence [23]. The prior study, from the Department of Psychiatry, Faculty of Medicine, Prince of Songkla University, identified that our schizophrenic patients had a moderate quality of life [24], and most patients and caregivers perceived a low level of stigma [13]. Moreover, most of the caregivers had no severe caregiver burden, with most burdens being at a mild level (22%).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast, the stigma of taking medication and having poor or no social support were found to negatively influence adherence [23]. The prior study, from the Department of Psychiatry, Faculty of Medicine, Prince of Songkla University, identified that our schizophrenic patients had a moderate quality of life [24], and most patients and caregivers perceived a low level of stigma [13]. Moreover, most of the caregivers had no severe caregiver burden, with most burdens being at a mild level (22%).…”
Section: Discussionmentioning
confidence: 79%
“…In addition, except for the relationship with the physician having evidence suggesting a therapeutic relationship with monitoring and introduction in medication intake or being contributors to appropriate adherence [22], other external or environment-associated factors included: the stigma of the illness, living situations, and caretaker support were also important. Other environmental factors that affect adherence positively include family or social support [24] and greater social activities [8]. In contrast, the stigma of taking medication and having poor or no social support were found to negatively influence adherence [23].…”
Section: Discussionmentioning
confidence: 99%
“…5 In contrast, the stigma of taking medication and having poor or no social support were found to negatively influence medication adherence. 25 The prior study, from the Department of Psychiatry, Faculty of Medicine, Prince of Songkla University, identified that these individuals with schizophrenia had a moderate quality of life 26 , and most patients and caregivers perceived a low level of stigma. 13 Moreover, most of the caregivers had no severe caregiver burden, with most burdens being at a mild level (22.0%).…”
Section: Teetharatkul T and Pitanupong J Meaning And Adherence In Sch...mentioning
confidence: 99%
“…It consisted of 15 items, and following translation into Arabic, the patient checked the boxes next to each one that applied to him. There are 6 reverse sentences (2,6,7,10,13,14). Responses were scored according to three categories: (1) Not at all, (2) occasionally, and (3) frequently.…”
Section: Tool (2) Emotional Intelligence Scalementioning
confidence: 99%